Abacus Games Foster Concentration and Socioemotional Skills in Early Childhood: Permainan Abacus Membantu Mengembangkan Konsentrasi dan Keterampilan Sosial-Emosional pada Anak Usia Dini - Siti Qomariah; Luluk Iffatur Rocmah (Academia Open, 2025)
General Background: Early childhood represents a critical developmental period in which appropriate educational stimulation can optimize cognitive, social, and emotional growth through play-based learning. Specific Background: Abacus activities are increasingly introduced in early childhood settings as playful numeracy tools that combine physical manipulation, rhythm, and structured tasks. Knowledge Gap: Prior studies have primarily emphasized symbolic thinking or arithmetic ability, leaving limited analysis of how abacus-based activities are implemented and how they relate holistically to multiple developmental aspects. Aims: This study aims to analyze the implementation of abacus games for children aged 5–6 years at a Raudhatul Athfal institution and to examine their developmental outcomes. Results: Using a qualitative phenomenological approach with interviews, observations, and documentation, the study found that the activity was conducted through five sequential stages—ice breaking, singing, introduction to the tool, practice tasks, and rewards—and was associated with improved concentration, self-confidence, discipline, and group cohesion. Novelty: The study provides a holistic description of both procedural implementation and multidimensional developmental outcomes within a natural classroom context. Implications: The findings suggest that structured abacus play can serve as an engaging educational strategy for early childhood educators seeking developmentally appropriate activities that integrate cognitive focus with socioemotional growth. Highlights: Activities followed a structured five-stage sequence from warm-up to reinforcement. Participants displayed greater attentional persistence during learning sessions. Classroom interactions reflected stronger cooperation among peers. Keywords: Abacus Games; Early Childhood Education; Concentration; Self-Confidence; Discipline